2010
DOI: 10.1093/eurheartj/ehq327
|View full text |Cite
|
Sign up to set email alerts
|

Cheyne-Stokes respiration and obstructive sleep apnoea are independent risk factors for malignant ventricular arrhythmias requiring appropriate cardioverter-defibrillator therapies in patients with congestive heart failure

Abstract: In patients with CHF, CSA and OSA are independently associated with an increased risk for ventricular arrhythmias and appropriate cardioverter-defibrillator therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
143
1
19

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 262 publications
(174 citation statements)
references
References 49 publications
11
143
1
19
Order By: Relevance
“…After a 48 month follow-up period, sleep disordered breathing was found to be independently associated with an increased risk for ventricular arrhythmias [94]. Moreover, OSA patients treated with catheter ablation for ventricular dysrhythmias seem to have a higher relapse rate compared to those without OSA (45% versus 6%) [95].…”
Section: Ventricular Arrhythmias Observational Studiesmentioning
confidence: 98%
“…After a 48 month follow-up period, sleep disordered breathing was found to be independently associated with an increased risk for ventricular arrhythmias [94]. Moreover, OSA patients treated with catheter ablation for ventricular dysrhythmias seem to have a higher relapse rate compared to those without OSA (45% versus 6%) [95].…”
Section: Ventricular Arrhythmias Observational Studiesmentioning
confidence: 98%
“…Many patients show a combination of different types of SDB breathing patterns that may change over the course of a night as well as over time 10. Although both OSA and CSA/CSR have been shown to be independent predictors of worse outcome in HF patients,11, 12, 13, 14, 15, 16 the different forms of SDB are likely to have different effects on the cardiovascular system 17. The findings of a post hoc analysis of the SERVE‐HF study provided some evidence that the impact of SDB and its treatment might be different in CSA and OSA, showing effect modification when the proportion of CSR at baseline was <20% 18.…”
Section: Introductionmentioning
confidence: 99%
“…When multivariate analyses were performed to control for potential confounders involved in determining outcome in patients with HF, CSA was an independent factor for death or cardiac transplantation in these patients 4,22,23) . Some large -scale studies have demonstrated that SDB is associated with occurrence of ventricular arrhythmias 20,24) and adverse prognosis in HF patients 25,26) .…”
Section: Impact Of Sdb In Hf Patientsmentioning
confidence: 99%